Dreams of Precision Manufacturing: Beavers Dental of Morrisburg, Ontario - McNally, Larry (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1995)
ABSTRACTIn 1946 George Beavers went to Germany and convinced Rudolf Funke to bring his superior dental bur technology to Canada. What resulted in Beaver's small factory in Morrisburg, Ontario was an amalgam of European and North American manufacturing technologies. This has enabled Beavers Dental to become the world's largest producer of dental burs.